ETCLIP - The Challenge of the European Carbon Market: Emission Trading, Carbon Leakage and Instruments to Stabilise the CO2 Price. Price Volatility in Carbon Markets: Why it Matters and How it Can be Managed - Claudia Kettner; Daniela Kletzan-Slamanig; Angela Köppl; Thomas Schinko; Andreas Türk (Austrian Institute of Economic Research (WIFO), 2011)
The environmental effectiveness of an emission trading system depends on the one hand on the stringency of the cap and on the other hand on the scheme's ability to provide stable regulatory conditions and incentives for investment in emission saving technologies. However, in case of highly volatile CO2 prices no clear investment signal is provided and hence firms' decision making and planning is rendered difficult. Analyses of price developments in the European Emission Trading Scheme (EU ETS) indicate that in Phase 1 (2005-2007) fluctuations were mainly caused by incomplete information at the beginning, adjustments after the emergence of verified emission data and regulatory mechanisms. At the beginning of Phase 2 (2008-2012) in contrast a decline in carbon prices was observed as firms sold surplus allowances resulting from lower emissions due to economic recession. For Phase 3 of the EU ETS (2013-2020) hence the introduction of price stabilisation measures has been suggested by several member countries during the discussions on the EU energy and climate package. Various instruments can be integrated in a cap-and-trade scheme in order to reduce price volatility such as provisions for banking and borrowing, the approval of offsets for compliance purposes and hybrid systems, i.e., combinations of price and quantity mechanisms. Given the long-term nature of climate policy, the related uncertainties regarding technological change and political frameworks, and given a rising speculation in carbon markets, such price stabilisation approaches should be considered for the future design of emission trading schemes.
Keywords: 330; Emissionshandel; Grenzüberschreitende Umweltbelastung; Treibhausgas-Emissionen; Internationale Umweltpolitik; EU-Staaten